ANALYSIS OF RESOURCES-BASED EDUCATION MANAGEMENT AND ITS’ EFFECT ON SCHOOL ADVANTAGE (Study on Vocation High School in the City and District of Bandung) - Rahayu, Agus; Suwatno, Suwatno; Suherman, Amay; Yuliawati, Ayu Khrisna (International Journal of Education, 2014)
Bandung SMKN (vocational high school) resources are relatively diverse. These resourcesmust be identified if they are to be utilized by the vocational high school in their effort to planand make the implement of their education program better than other vocational high schools.Therefore it is necessary to analyze further the current condition of school resources as theresources theoretically can be developed to produce a competitive edge for the education unit.This research is focused on efforts to analyze the SMKN resources in Bandung with intentionto develop them to strengthen planning and implementation of vocational education. The resultof the research produced a model for implementation of vocational high school resources.This model focuses on education management practice, development and implementationof curriculum, development and implementation of learning resources, development andimplementation of teachers as human resources in the vocational high school.Keywords: Resources, strategy and school competitiveness, Vocational High School.